Insecticide effect of leaf extracts from Schinus molle on larvae of Gonipterus platensis (2017)
The insecticide effect of new and mature leaf extracts obtained with ethanol and water from Schinus molle L. (Anacardiaceae) were evaluated at 0.5 - 3.4% w/v, and 0.5 - 4.8% w/v, respectively, onto larvae of Gonipterus platensis Marelli (Coleoptera: Curculionidae), an important defoliating pest on eucalypt (Eucalyptus spp., Myrtaceae) plantations. The extracts were applied to eucalypt leaves that were given as food to the larvae, and their effects were determined by determining mortality and the LC50 and LT50 by Probit analysis on the larvae. Both extracts were efficacious, especially those from new leaves; the ethanol extract from them caused the greatest mortality. The highest concentrations of the water and ethanol extracts (3.4 and 4.8% w/v, respectively) caused average mortality of 100 and 88.9% with new leaf extracts, and 94.7 and 86.4% with mature ones, respectively. The insecticide effectiveness 6 d after treatment in decreasing order were: new-ethanol (LC50 = 0.79% w/v), new-water (LC50= 2.08% w/v), mature-ethanol (LC50=0.63% w/v) mature-water (LC50=12.01% w/v). The LT50 at 1.7% w/v was 5.2 d. These results of the insecticide effect on G. platensis larvae allow to consider the leaf extracts from S. molle an interesting alternative as a bioinsecticide source for integrated pest management of this pest.